Oncolytic Viruses: Immunotherapy Drugs for Gastrointestinal Malignant Tumors - Li, Qingbo; Oduro, Patrick Kwabena; Guo, Rui; Li, Ruiqiao; Leng, Ling; Kong, Xianbin; Wang, Qilong; Yang, Long (Frontiers in Cellular and Infection Microbiology, 2022)
Oncolytic virus therapy has advanced rapidly in recent years. Natural or transgenic viruses can target tumor cells and inhibit tumor growth and metastasis in various ways without interfering with normal cell and tissue function. Oncolytic viruses have a high level of specificity and are relatively safe. Malignant tumors in the digestive system continue to have a high incidence and mortality rate. Although existing treatment methods have achieved some curative effects, they still require further improvement due to side effects and a lack of specificity. Many studies have shown that oncolytic viruses can kill various tumor cells, including malignant tumors in the digestive system. This review discusses how oncolytic virus therapy improves malignant tumors in the digestive system from the point-of-view of basic and clinical studies. Also, the oncolytic virus anti-tumor mechanisms underpinning the therapeutic potential of oncolytic viruses are expounded. In all, we argue that oncolytic viruses might eventually provide therapeutic solutions to malignant tumors in the digestive system.